Ginsenoside Compound K Attenuates Ox-LDL-Mediated Macrophage Inflammation and Foam Cell Formation via Autophagy Induction and Modulating NF-κB, p38, and JNK MAPK Signaling - Lu, Shan; Luo, Yun; Sun, GuiBo; Sun, XiaoBo (Frontiers in Pharmacology, 2020)
Atherosclerosis is a major reason for the high morbidity and mortality of cardiovascular diseases. Macrophage inflammation and foam cell formation are the key pathological processes of atherosclerosis. Ginsenoside compound K (CK) is a metabolite derived from ginseng. CK has anti atherosclerotic effect, but the molecular mechanism remains to be elucidated. We aim to explore the protective effect of CK against ox-LDL-induced inflammatory responses and foam cells formation in vitro and explore its potential mechanisms. Through the results of oil red O staining, Western blot, and qPCR, we found that CK significantly inhibited the foam cell formation, reduced the expression of SR-A1 and increased ABCA1 and ABCG1 expression. In addition, CK increased the number of autophagosomes and upregulated the LC3II/LC3I ratio and the expressions of ATG5 and Beclin-1 but decreased p62 expression. Moreover, CK significantly inhibited the NF-κB, p38, and JNK MAPK signaling pathway. Altogether, CK attenuated macrophage inflammation and foam cell formation via autophagy induction and by modulating NF-κB, p38, and JNK MAPK signaling. Thus, CK has potential as a therapeutic drug for atherosclerosis.